A clinical case of a generalized infection caused by Yersinia enterocolitica in a serviceman - E.M. Khoroshun; K.I. Bodnia; V.A. Mishchenko; V.V. Nehoduiko; V.V. Kondratyuk; V.V. Pavliy; M.B. Pushkar (Медицина неотложных состояний, 2025)
Yersiniosis is a disease that can mimic the clinical picture of other diseases: acute respiratory viral infections, scarlet fever, intestinal infection, appendicitis, sepsis, rheumatism, mononucleosis, etc. This leads to diagnostic errors and requires considering the possibility of contamination of food and water with rodent excrement in places of deployment of personnel in wartime conditions. In this case, the infection caused by Yersinia enterocolitica in a serviceman was not detected in a timely manner and acquired a generalized course. Timely diagnosis and prescription of antibacterial therapy at the prehospital stage will contribute to the rapid recovery of servicemen and the avoidance of undesirable complications of the disease.